2017
DOI: 10.1039/c6cp08553a
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of protonated glutamic acid at room and cryogenic temperatures

Abstract: Recognition properties of biologically relevant molecules depend on their conformation. Herein, the conformation of protonated glutamic acid (HGlu) isolated in quadruple ion traps is characterized by vibrational spectroscopy at room and cryogenic temperatures and dispersion-corrected density functional theory calculations at the B3LYP-D3/aug-cc-pVTZ level. The infrared multiple photon dissociation (IRMPD) spectrum recorded in the fingerprint range at room temperature using an IR free electron laser is attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 62 publications
2
31
0
Order By: Relevance
“…As underlined by Alonso et al [35] an inversion in the hydrogen bonding network in the water cluster leads to two similar isomers for the BPL:(H 2 O) 4 complex. Similarly, our calculations also lead to the prediction of two almost isoenergetic isomers for the BPL:(H 2 O) 5 complex, differing from one another by an inversion in the hydrogen bonding network in the water cluster.…”
Section: Methods Calibrationmentioning
confidence: 89%
See 2 more Smart Citations
“…As underlined by Alonso et al [35] an inversion in the hydrogen bonding network in the water cluster leads to two similar isomers for the BPL:(H 2 O) 4 complex. Similarly, our calculations also lead to the prediction of two almost isoenergetic isomers for the BPL:(H 2 O) 5 complex, differing from one another by an inversion in the hydrogen bonding network in the water cluster.…”
Section: Methods Calibrationmentioning
confidence: 89%
“…It was found that both isomers of the BPL:(H 2 O) 4 5 isomers involve similar water-solute interactions, as demonstrated by the QTAIM analysis. The above-described structures suggest that the following features of the solvent cluster may favor an efficient facial-parallel interaction with BPL: four almost coplanar water molecules with two consecutive electron-rich regions (oxygen atoms) that may interact with the electrondeficient region of the BPL (hydrogen atoms of the -CH 2 -groups), and two consecutive electron-deficient regions (hydrogen atoms) that may interact with the electron-rich region of the BPL (ester function).…”
Section: Methods Calibrationmentioning
confidence: 90%
See 1 more Smart Citation
“…As a consequence, only two almost isoenergetic isomers are observed in the gas phase. 47,51,52 Recently, our IRPD spectra of cryogenic GluH + revealed their relative abundance as approximately 2 : 1, showing the importance of cryogenic cooling, single-photon absorption conditions, and consideration of the XH stretch range (2600-3600 cm À1 ) for the identification of molecular conformation. 51 IR spectra and quantum chemical analysis of alkali-metalated GluM + (M = Li-Cs) revealed cation size-dependent conformational locking by HOCOÁ Á ÁM + Á Á ÁOCOH bridges.…”
Section: Introductionmentioning
confidence: 87%
“…47,51,52 Recently, our IRPD spectra of cryogenic GluH + revealed their relative abundance as approximately 2 : 1, showing the importance of cryogenic cooling, single-photon absorption conditions, and consideration of the XH stretch range (2600-3600 cm À1 ) for the identification of molecular conformation. 51 IR spectra and quantum chemical analysis of alkali-metalated GluM + (M = Li-Cs) revealed cation size-dependent conformational locking by HOCOÁ Á ÁM + Á Á ÁOCOH bridges. [52][53][54] Herein, we apply cryogenic infrared photodissociation (IRPD) and IR-IR hole burning spectroscopy and first-principles simulations to homochiral (LL) and heterochiral (LD) glutamic acid dimers (LL-/LD-Glu 2 H + ) to determine their structures, energies and eventually their chirality recognition.…”
Section: Introductionmentioning
confidence: 87%